Coexistence of neuroblastoma and ganglioneuroma in a girl with a hemizygous deletion of chromosome 11q14.1–23.3. Issue 2 (13th October 2015) - Shiohama, Tadashi; Fujii, Katsunori; Hino, Moeko; Shimizu, Kenji; Ohashi, Hirofumi; Kambe, Michiyo; Nakatani, Yukio; Mitsunaga, Tetsuya; Yoshida, Hideo; Ochiai, Hidemasa; Shimojo, Naoki
Abstract : Constitutional 11q interstitial deletion syndrome presents with congenital anomalies including microcephaly with craniostenosis, minor dysmorphic features, vitreoretinopathy, and renal anomalies. This syndrome is occasionally associated with neuroblastoma (NB) as a life‐threatening complication, which is important for clinical care. Although the corresponding locus to NB has been predicted to exist in 11q22–23 by previous deletion studies related to NB, the causative haploinsufficient genes have not yet been identified. We herein reported for the first time the simultaneous coexistence of adrenal NB and abdominal prevertebral ganglioneuroma in a 6‐year‐old girl with a constitutional hemizygous 11q14.1–23.3 deletion. Of the 11 haploinsufficient genes predicted with an in silico database, we focused on NCAM1 and CADM1 as the genes accountable for NB and ganglioneuroma. The deletion range, especially the 11q22.3 involvement, needs to be determined in 11q deletion cases in order to predict susceptibility to peripheral nerve tumors involving NB and ganglioneuroma. © 2015 Wiley Periodicals, Inc.